2006
DOI: 10.1088/1742-5468/2006/01/p01008
|View full text |Cite
|
Sign up to set email alerts
|

Optimization in random field Ising models by quantum annealing

Abstract: We investigate the properties of quantum annealing applied to the random field Ising model in one, two and three dimensions. The decay rate of the residual energy, defined as the energy excess from the ground state, is find to be eres ∼ log(NMC ) −ζ with ζ in the range 2...6, depending on the strength of the random field. Systems with "large clusters" are harder to optimize as measured by ζ. Our numerical results suggest that in the ordered phase ζ = 2 whereas in the paramagnetic phase the annealing procedure … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…We show that the power decay (21) satisfies the adiabaticity condition (17) which guarantees convergence to the ground state of H Ising as t → ∞. .…”
Section: Transverse Field Ising Modelmentioning
confidence: 88%
See 2 more Smart Citations
“…We show that the power decay (21) satisfies the adiabaticity condition (17) which guarantees convergence to the ground state of H Ising as t → ∞. .…”
Section: Transverse Field Ising Modelmentioning
confidence: 88%
“…Here a and c are constants of O(N 0 ) and δ is a small parameter to control adiabaticity appearing in (17).…”
Section: Transverse Field Ising Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Introduction of transverse ferromagnetic interactions does not necessarily improve the result for the cases of disordered ground states. This observation is to be compared with the finding of Sarjala et al [13] who showed by quantum Monte Carlo simulations that quantum annealing by the conventional method is less efficient than simulated annealing when the ground state is strongly ferromagnetic. We may conclude that their consequence does not necessarily reflect intrinsic features of quantum annealing.…”
Section: B Resultsmentioning
confidence: 85%
“…The logarithmic scaling was recently supported by the quantum Monte-Carlo simulation [7], though the evolution of state in quantum Monte-Carlo is different from the one ruled by the Schrödinger equation. In contrast, the authors of this paper have shown another scaling law of residual energy given by…”
mentioning
confidence: 95%